At the crossroads: Lessons and challenges in computational social science - Borge-Holthoefer, J; Moreno, Y; Yasseri, T (Frontiers Media, 2016)
With tools borrowed from Statistical Physics and Complexity, this new area of study have already made important contributions, which in turn have fostered the development of novel theoretical foundations in Social Science and Economics, via ...